THE COOPERATIVE PRINCIPLE VIOLATION IN CLASSROOM TEACHING LEARNING PROCESS - Hutahaean, David Togi (Universitas Wiralodra, 2020)
The purpose of this research is to investigate the cooperative principle violation between the teacher and the students in grade eighth classroom teaching and learning process in SMP N 11 Pematangsiantar. The problem of this research was What cooperative principle are violated by the teacher and the students in grade eighth classroom teaching and learning process in SMP N 11 Pematangsiantar, To solve the problem, the researchers use some theories like: Grundy (2000), Yule (1996), Cruse (2000), Cook (1989), Cutting (2002), Moloeong (2007), Grice (1975). The research done in this study follows descriptive qualitative perspective. Source data in this study is the cooperative principle violation between the teacher and the students in grade eighth classroom teaching and learning process in SMP N 11 Pematangsiantar. Descriptive research describes what it is. It involves the descriptions, recording, analysis, and interpretation of conditions that exist. After analyzing the data, the researchers conclude that the maxim are flouted if the information is more informative than is required, ambiguous, uses symbolic, not absolutely true, lack of adequate evidence. The maxim can be flouted when the researcherss produce some utterances in the form. From the data can found the maxim, they are: maxim of Quality, maxim of Quantity, maxim of Relevant, maxim of Manner. The maxim flout when the conversation started until the end, so the maxim can used in the conversation and the conversation can analyze with the maxim.